The concept of Islam Hadhari as reflected in Thirukkural - Maniam, K. (2014)

(untitled)
As a multiracial nation, Malaysia has the potential to accept various thoughts and life philosophy from the illustrious text of each community. It is evident that the concept of Islam Hadhari introduced by YAB Datuk Seri Abdullah Alunad Badawi shares a lot of similarities with Thirukkural. The three elements namely economy, social and politics are emphasized in these two doctrines. But the vast difference is Islam Hadhari holds on to Allah whereas Thirukkural adheres to 'the merciful God'. Yet this is not contrary to the concept of 'God' stipulated in these two texts. So it is evident that the faith in God is very much emphasized in both Thirukkural and Islam Hadhari. Good and diligent government gives importance to intelligence and moral in an administration. The possession of power and economy must be in accordance with rules of Islam Hadhari. Thirukural teaches equality and prudence in economy management. Islam hadhari and Thirukkural prioritises the perseverance of nature. It is one of the similarities.